STUDI KONDISI LIMNOLOGIS WADUK SERMO PADA TAHAP PRA-INUNDASI - Bambang Triyatmo (Universitas Gadjah Mada, 2001)
A study on the limnologic conditions of Sermo reservoir was conducted from September 1996 to January 1997. Water samples were collected from six stations every ± 25 days. The samples from each station were collected from 2 to 3 different depths of water. The objectives of this research were to know the physically, chemically and biologically water quality of Sermo reservoir. Results indicated that the water quality of Sermo reservoir was suitable for fishes. The concentration of NH4+, NO3-, PO43-, dan SO4= indicated that the water fertility could support the growth of plankton as natural food for fishes and other aquatic organisms. However, the water quality and its productivity have not been stabile yet. Phytoplankton was more dominance than zooplankton. Number of phytoplankton species were between 10 - 15 species, that was dominated by Nitzschia sp., Nostoc sp. and Peridinium. Zooplankton species observed were Brachionus sp. and Cyclops sp. Any aquatic plants were not found.